Nigeria Manpower Needs and Opportunities in Freshwater Fish Seed Production - Kareeem, O. K; Olanrewaju, A. N.; Olaosebikan, B. D. (The Nigerian Journal of Rural Extension and Development, 2023)
Aquaculture is presently recognized as having a steady growth in Nigeria, however, the sustainability of its contribution to food security is hinged on availability of quality fish seed from hatcheries for stocking. Unfortunately, most hatcheries in the country are managed by quack whose actions or inactions kill people interest in aquaculture business. Therefore, a major constraint to steady contribution of aquaculture sub sector to the economic growth of the country is lack of adequately skilled manpower especially in the area of fish seed production. For aquaculture to ultimately provide the much needed employment and wealth for sustainable economic growth, adequately equipped, skilled and experienced manpower must be available. Urgent need arises for skilled personnel in the area of Broodstock development and management, Fish Seed Production, Geneticists and Ecologists to continually boost fish production. These will lead to arrays of opportunities for employment generation, food security and economic transformation. This paper therefore reviews the manpower need and opportunities in freshwater fish seed production in Nigeria.